What Does the Minimum Wage Do? - Belman, Dale; Wolfson, Paul J. (W.E. Upjohn Institute, 2023)
This book make sense of the scores of research studies on the minimum wage that began in the early 1990s. The authors look at who is affected by the minimum wage, both directly and indirectly; which observable, measurable variables (e.g., wages, employment, school enrollment) the minimum wage influences; how long it takes for the variables to respond to the minimum wage and the size and desirability of the effect; why the minimum wage has the results it does (and not others); and the workers most likely to be affected by changes to the minimum wage.